Associations of volatile organic compounds/semi-volatile organic compounds exposure on asthma: A review of epidemiological studies and diagnostic applications - Tiantian GU; Jin ZHANG; Teng YANG; Jiawei WANG; Qinsheng KONG; Guoxing LI; Jing HUANG (环境与职业医学)
Volatile organic compounds (VOCs) and semi-volatile organic compounds (SVOCs) are common organic compounds in indoor and outdoor air, and enter the human body primarily through the respiratory tract and directly damage the respiratory system. Previous studies have suggested that exposure to VOCs/SVOCs may associate with the prevalence, incidence, and progression of asthma, but the extent of the associations is still vague. Furthermore, biomarkers for efficient and simple asthma diagnosis, typing, and attack prediction remain unclear at this stage. From the perspective of the collection and detection methods of VOCs/SVOCs, this paper summarized the epidemiological associations and underlying biological mechanisms between VOCs/SVOCs exposure and the prevalence, incidence, and progression of asthma in children/adults. It also demonstrated the application of VOCs/SVOCs in recent years in assisting asthma diagnosis, such as distinguishing asthma patients from the healthy population, differentiating different asthma phenotypes, and predicting asthma acute exacerbations, aiming to provide a scientific basis for improving current asthma management.